UPAYA PENINGKATAN PENDAPATAN USAHA GARMEN SUBHAN DAN SABLON BUDI - Suryandari, Ni Nyoman Ayu; Primadewi, Siluh Putu Natha; Novitasari, Ni Luh Gde (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
Along with the rise of Bali tourism from the Bali bombings that can not be denied affecting the export market of apparel in Bali, garment business is now starting to rise again. The products produced by garment entrepreneurs are also increasingly varied and creative. This is evidenced by the increasing number of garment entrepreneurs both multi-national scale, international, and home-based. Generally, nowadays, international and national garment entrepreneurs are handing out the process of sewing and coloring to smaller (home) entrepreneurs to get cheaper prices and the cost of production can be suppressed by large entrepreneurs. Partners in this program are two IRT Subhan and IRT Concerned Budi Utomo. Subhan garment business and screen printing business Budi is one of the many small entrepreneurs (home) who became business partners of multi-national and international garment entrepreneurs in Denpasar. This program is interesting to implement because both partners have the potential to grow but the business is still home industry that still use the machine with limited amount and manual processing. The results that have been achieved in this program involves three aspects namely aspects of production and management aspects. Aspects of production include the procurement of pleret machines, press machines, screen printing tables, and the arrangement of production space. From the aspect of management is done counseling and guidance of simple way bookkeeping. The other result has been achieved in the form of teaching materials. The targets in this program are scientific publications on journals, increasing quantity and quality of products with the addition of plating machines, press machines and screen printing desks, improving understanding of simple bookkeeping, and increasing turnover on partners with new engine procurement.